Human life and self-realization according to Edith Stein - Galvani, Martina (Aoristo - International Journal of Phenomenology, Hermeneutics and Metaphysics, 2021)
The aim of this article is to analyse the Edith Stein’s phenomenological-metaphysical anthropology and its moral aspects. Her enquiry shifts from the study of those aspects common to both human beings and animals to an aspect that is specifically and exclusively human, i.e., spirituality. The person only is a spiritual subject, because he has an intellectual knowledge and he can freely act. In this investigation, Stein moves from outcomes achieved thanks to the phenomenological method, which leads her to focus on a description of the bodily, psychical and spiritual sphere of the human being. Accordingly, Stein reflects on the ethical consequences of her anthropological research. Following Augustine, she perceives originary self-consciousness as interiority, from which to begin explicating intellectual knowledge, and especially free action and hence ethics. Action is not only expressed outwards, first of all it is self-actuation – acting and being are mutually implied. The direction of moral actions is thus already present in each one’s individual ‘essence’ (Wesen) and this essence, thanks to the creative ‘essentiality’ (Wesenheiten), is ab eterno in Logos. In view of this complex theological node, Stein recognizes Christ as the archetype of the only possible ethics.